2023
DOI: 10.1057/s41599-023-01941-2
|View full text |Cite
|
Sign up to set email alerts
|

Green bond issuance and corporate ESG performance: the perspective of internal attention and external supervision

Abstract: Based on the staggered difference-in-difference (DID) model, this paper uses Chinese listed firms between 2012 and 2020 to investigate the impact of green bond issuance on corporate environmental, social and governance (ESG) performance. We provide evidence that green bond issuance positively enhances corporate ESG performance. Green bond issuance mainly promotes corporate ESG performance through the internal attention effect and the external supervision effect. Moreover, the positive correlation between green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Utilizing a linear model, we established the impact of NSC on mechanism variables. Subsequently, it conducts a comparative analysis of the estimated coefficients of NSC in equations that control for mechanism variables and those that do not, aiming to validate the existence of such mechanisms (Gao and Yuan, 2020;Zhang and Wang, 2022;Chen et al 2023a).…”
Section: Control Variablesmentioning
confidence: 99%
“…Utilizing a linear model, we established the impact of NSC on mechanism variables. Subsequently, it conducts a comparative analysis of the estimated coefficients of NSC in equations that control for mechanism variables and those that do not, aiming to validate the existence of such mechanisms (Gao and Yuan, 2020;Zhang and Wang, 2022;Chen et al 2023a).…”
Section: Control Variablesmentioning
confidence: 99%
“…There are usually three theories to explain the issuance of green bonds by enterprises: First, signal theory [20]. By issuing green bonds, enterprises can convey their determination to support environmental protection to the outside world, gain attention from the securities market and investors, and enhance social reputation and corporate value [3,11,21]. In addition, the issuance of green bonds by enterprises conveys their commitment to environmental protection to the outside world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is particularly noteworthy that since the implementation of the green bond policy, the issuance scale of green bonds in China has continued to grow, reflecting the strong market demand and recognition of this financial instrument. By the end of 2022, China has ranked among the top in the global green bond market [11]. According to the data of China Bond Information Network (CBIN) Green Bond Environmental Benefit Information Database [10,12,13], China issued more than 600 billion RMB green bonds in 2022, reaching a record high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have found that corporate environmental information disclosure can improve corporate environmental and financial performance (Wang et al, 2016;Khatri and Kjaerland, 2023), and the more detailed the environmental information disclosed by companies, the easier it is to obtain bank loans (John and Reisz, 2020;Bharath et al, 2008;Goss and Roberts, 2011). On the one hand, the implementation of green finance policies such as the issuance of green bonds has actively improved the ESG performance of enterprises (Chen et al, 2023). On the other hand, the implementation of green credit policy encourages financial institutions to pay full attention to the fulfillment of companies' environmental responsibilities, and encourages companies to actively disclose environmental information by effectively linking corporate financing needs with environmental responsibilities (Wang et al, 2019), which further improves the quality of corporate environmental information disclosure (Aizawa and Yang, 2010).…”
Section: Relationship Between Environmental Information Disclosure An...mentioning
confidence: 99%